Legal Capacity of Children and Adolescents: The Realization of Rights - Ruiz, Diana Patricia Restrepo; Monroy, Rodrigo Pérez; Avilés, Hillary Patricia Herrera (Journal of Ecohumanism, 2024)
The recognition of children and adolescents (hereinafter NNA, by its Spanish acronym) as full rights-holders under the Convention on the Rights of the Child (CRC) marked a turning point in the history of childhood and adolescence regarding the protection of their rights. Even so, this declaration did not give rise to legal mechanisms allowing this population group to assert these rights on their own, creating a normative contradiction. The CRC itself provided State Parties with a principle that can help overcome this obstacle: progressive autonomy, which aims to counteract institutions rooted in classical Roman law—still unfortunately in force in most legal systems—such as the legal incapacity to act. Through legal hermeneutics, applying the methodology derived from legality analysis and coherence analysis, this study demonstrates how to transcend the limitations on NNA’s legal capacity imposed by the Civil Code, and how to incorporate progressive autonomy while correcting oversights observed in countries that have implemented it for several years. It also rethinks the material criterion for standing (legitimacy in the cause) to include minors, and proposes ways to engage the educational system in shaping legally aware individuals who understand not only their rights and duties but also their active role in defending and protecting those rights.